A family support intervention to reduce stress among parents of preterm infants in neonatal intensive care unit - Abdeyazdan, Zahra (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Preterm infants constitute a large proportion of the newborn population in the neonatal intensive care units (NICUs). Parents, as the main members of the care team, are not adequately supported as the focus is chiefly on infant care. The present study aimed to evaluate the effect of a family support intervention on the stress levels among the parents of preterm infants in NICU. MATERIALS AND METHODS: In this quasi-experimental study, convenience sampling method was used to select 50 parents of preterm infants. The subjects were allocated to two groups of intervention and control (n = 25 pairs in each). While the control group received routine care, the intervention group benefitted from a two-stage family support program (including informational and observational phases in the first stage and emotional supportive intervention in the second). The Parental Stressor Scale-NICU (PSS-NICU) was completed by both fathers and mothers of the two groups (before and after intervention). Descriptive and inferential statistics were employed to analyze data in SPSS version 18. RESULTS: Before the intervention, the mean total scores of PSS-NICU and also the mean scores of its three subscales were not significantly different between the two groups. However, after the intervention, significant differences were observed between the two groups. The scores of the intervention group showed significant reduction following the intervention, but such a difference was not detected in the control group. CONCLUSIONS: Apparently, early educational and emotional support for parents of preterm infants decreased their stress. Similar interventions may thus be effective in empowering parents for caring of their infant and playing their parental role.